Change of Serum Biomarkers to Post-Thrombolytic Symptomatic Intracranial Hemorrhage in Stroke - Cui, Yu; Wang, Xin-Hong; Zhao, Yong; Chen, Shao-Yuan; Sheng, Bao-Ying; Wang, Li-Hua; Chen, Hui-Sheng (Frontiers in Neurology, 2022)
Background: Symptomatic intracranial hemorrhage (sICH) is a terrible complication after intravenous alteplase in stroke, and numerous biomarkers have been investigated. However, dynamic response of biomarkers to sICH has not been well determined. Aims: To investigate association between dynamic change of biomarkers and sICH. Methods: This is a prospective cohort study and patients with sICH within 24 hours after thrombolysis were enrolled, while patients without sICH were matched by propensity score matching with the ratio of 1:1. The blood samples were collected prior to and 24 hours after intravenous thrombolysis, and preset 49 serum biomarkers were measured by microarray analysis. Protein function enrichment analyses were performed to detect the association between dynamic change of biomarkers and sICH. Results: Of consecutive 358 patients, 7 patients with sICH in 24 hours were assigned as sICH group, while 7 matched patients without any ICH were assigned as Non sICH group. A total of 9 biomarkers were found to significantly change prior to vs after thrombolysis between groups, including increased biomarkers such as brain-derived neurotrophic factor, C-C motif chemokine ligand (CCL)-24, interleukin (IL)-6, IL-10, IL-18, and vascular endothelial growth factor, and decreased biomarkers such as CCL-11, intercellular adhesion molecule-1, and IL-7. Conclusions: This is the first study to identify dynamic changes of serum biomarkers in patients with sICH after intravenous thrombolysis, and found that 6 neuroinflammatory and 3 neuroprotective biomarkers may be associated with brain injury following post-thrombolytic sICH. Clinical Trial Registration: https://www.clinicaltrials.gov; identifier: NCT02854592.